VATSONGA PEOPLE’S PERCEPTIONS OF CHILDREN’S RIGHTS - Simbine, Lisenga; Le Roux, Liana (Social Work/Maatskaplike Werk, 2021)
This article is based on the findings of a qualitative study that explored the Vatsonga people’s perceptions of children’s rights to protection. Semi-structured interviews were conducted with 40 community-based participants and 11child protection social workers who were familiar with the Vatsonga people's cultural heritage. Key informant and snowball sampling techniques were employed to select the community-based participants and availability sampling for selecting the social work participants. The study established that the Vatsonga people recognise the provision, protection and participation rights of children. Child participation is perceived as comprised of childhood responsibilities, not the right to be heard perse. The paper argues that some of the purported violations of child rights in Africa emanate from the universal application of a Eurocentric worldview of children’s rights. We conclude that to understand child rights in Africa, African people should be allowed to contribute to the construction of an indigenised and contextualised perspective on child rights.